Examining the Effects of Probiotics on Athletes: A Review - Błaszczyński, Gustaw; Nowotarska, Agnieszka; Nojek, Paweł; Pawlik, Wiktoria; Zimonczyk, Mariusz; Zawół, Monika (Journal of Education, Health and Sport, 2024)
Introduction and Objective. Probiotics, defined as live microorganisms that provide health benefits when consumed in sufficient quantities, have gained attention in the sports community. The surge in popularity of long-distance athletic competitions such as marathons, triathlons, and cycling races has led to heightened rivalry and a rising curiosity in strategies to improve sports performance. Studies have suggested that probiotics could be a valuable aid for athletes looking to improve their well-being and overall progress. Methods. A literature review was conducted using PubMed and Google Scholar with search terms like "probiotics", "gut microflora", "probiotics in sport", "human microbiome", "athletic performance", "human microbiome", “diet supplementation” and related variations. Articles published within the last five years were prioritized. Brief description of the state of Knowledge. Probiotic supplementation has been shown to positively impact the health and performance of athletes, primarily through modulation of the microbiota-gut-brain axis. This review examines the influence of probiotic supplements on athletic performance, focusing on their effects on gut microbiota, immune support, mental health, anti-inflammatory properties, and overall performance enhancement. Conclusions. ​​Probiotics have been found to have numerous health benefits within the microbiota-gut-brain axis, making them an emerging area of research in athletes. The aim of this research is to understand the potential impacts on athletes experiencing health issues such as gastrointestinal symptoms, lowered immune system, mental disorders, excessive inflammation, or those looking to improve endurance and performance.